Implementasi Creative Art dalam Bermain Peran untuk Meningkatkan Perkembangan Bahasa dan Sosial Anak Usia Dini - Siti Khodijah (Universitas Muhammadiyah Enrekang, 2022)
This study aims to find out the Creativity Art model in role play to language development and social. This research method is research development (reserch and development / R & D) by going through four stages namely define, design, development, disseminate. The population of this study is the student group B RA Al Kautsar Indrapura consisting of 20 children, researchers took 5 children as a random sample. Instrument data collection in the form of observation sheet, data analysis using t test. The findings of this research is an increase in language development ability of children by 90% and 72% increase in social of children after treatment using creative art model in role play. While the use of conventional models of language development capability increase only 79% and social care increased by 54%. Thus it can be concluded that the use of creative art models in role play more effectively improve the ability of language development and social care of children compared with the use of conventional model.